THE IMPLEMENTATION OF RESEARCH-BASED TEACHING METHOD IN THE ENGLISH FOR ACADEMIC WRITING COURSE - Marisca Revani Putri (Acitya: Journal of Teaching and Education, 2019)
Writing has been regarded as the most difficult language skills since students in Indonesia were not familiar with this skill in the early and middle education level. On the other hand, in higher education level the students should produce a thesis to complete their study. Facilitating the students to ready for the thesis writing, English for Academic Writing course was delivered to the students. Research-based teaching method was implemented in the course in order to help the students improved their writing skills. The purpose of this research was to investigate the implementation of the research-based teaching method in the English for Academic Writing course. Case study was implemented to reach the conclusion. Thirty seven (37) Global Class students majoring in Information Technology were observed to gain the data. Questionnaire result was also used to support the observation data. The result showed that the students had improvement in writing skills after implementing the research-based teaching-learning method, especially the skills in citation, referencing, quoting, and paraphrasing. Besides, the feedback from the lecturer had a significant role in the implementation of research-based teaching method. This method also could facilitate the students to gain the knowledge and skills related to their field of study, in this case in the information technology field. This method also helped the students to improve and implement the 21st century skills such as critical thinking, collaboration, information literacy, technology literacy, initiative, and productivity.